A new approach for cost-benefit analysis of innovations to enhance smallholder farmers' resilience - Kramer, Berber; Timu, Anne G (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Enhancing smallholder farmers’ resilience has become an important objective for innovations in agricultural development. Cost-benefit analyses (CBA) of such innovations are essential in guiding future investments in agricultural development, but existing CBA methods often face challenges embedding non-monetary outcomes related to resilience. Resilience-enhancing innovations typically not only increase average incomes, but may also affect the variance of that income, and related welfare benefits depend on a beneficiary’s risk preferences. In addition, CBAs are typically unable to quantify costs and benefits in terms of gender-related outcomes such as women’s empowerment, or time use for women and men. This paper introduces a new approach to quantify costs and benefits related to such outcomes and demonstrates the approach using a case study of climate information services in Ghana. We argue that this is a more comprehensive method for impact assessment of innovations to enhance smallholder farmers’ resilience, enabling evidence-based investment prioritization.